Community Development Planning of PT. Elva Primandiri's Revitalization of Limbangan Traditional Market Project - Putra, R. Dimas Dwinovanto; Rudito, Bambang (Journal of Business and Management, 2014)
AbstractÃ¢â‚¬â€Quiddity of a man as social being, supporting human to live together and perform trading. Trading activity which continue to evolve, driven human to create trading instruments, one of which is the market, and more specifically, traditional market in Indonesia. It is believed that the Traditional Market is a driven factor of the economic wheel. Development of traditional market began to found barriers because of many factors underlying, starting from consumer lifestyle changes to the not-representative infrastructure condition. It is feared that the traditional market will die in the future. Revitalization of Limbangan Traditional Market Project hosted by the Local Government of Garut is a project that engages the sustainable development. The author conducted a study of community development planning activities to be carried out by PT. Elva Primandiri. As a company, PT. Elva Primandiri has social responsibility that must be met in addition to activities that aim to financial profit. Social responsibility is something that is associated with engagement with stakeholders and local communities. The author conducted an applied research with qualitative method which is social mapping that aimed to plan a program. This research includes the capability of the project, society ethnography, social network analysis, and focus group discussion (FGD). The output of this research are the management plan for community development and community development programs.Ã‚Â KeywordsÃ¢â‚¬â€ traditional market revitalization, social capital, community development, sustainable development, stakholders, social mapping, empowerment